An integration of weed management practices in potato un der New Alluvial soil (The Journal of Plant Protection Sciences, 2023)
To study the effect of different weed control measures on the yield of potato, a field experiment was carried out  with this crop (var. Kufri-Jyoti) for two consecutive years (2009-10; 2010-11) at ‘C’ Block farm of Bidhan  Chandra Krishi Viswavidyalaya, Kalyani, Nadia, West Bengal. The experiment was laid out in RBD with nine  treatments replicated thrice. The predominant weed flora in the experimental field of potato was Cyperus rotundas,  Chenopodium album, Anagallis arvensis and Fumaria purviflora. The results revealed that the maximum tuber  yield and return per rupee invested vis-à-vis the maximum N, P, K uptake by potato and the minimum uptake of N,  P and K by weeds emerged in the potato field were recorded under the treatment T3 (hand weeding at 20 DAP  along with mulching) which was closely followed by the treatment T9 (Pendimethalin @1kg a.i. ha-1along with mulching). So, the findings of the experiment provide us with a great opportunity of using herbicides and mulching  in combination to cope up with the labour crisis and minimize the cost of cultivation, therefore, maximizing benefit  cost ratio.
Keywords: Weed management; potato; new alluvial soil